PEMILIHAN JENIS PERKERASAN JALAN KABUPATEN BERDASARKAN KONDISI EKONOMI DAERAH - Wangsadinata, Wiratman; Tjahjani, A.R. Indra; Najid, Najid (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Pavement type selection in Indonesia in general is still determined by the strength of the subgrade. Type used for flexible pavement subgrade CBR values ​​are high and rigid strength for low CBR value. Based on the data path growth, data use basic information about the strength of the soil, resulting in significant long paths. This research will produce a mathematical model that can be used to determine the selection of the regent road pavement using variables including the traffic volume, population, budget allocation roads, topography, and accessibility. Limitation of road building is for district roads with different topographies review. The resulting model is expected to be used by decision makers at the district level so that the right type of pavement selected so that the acquisition of the allocation of funds can be used to construct a longer path.